Interannual Variability of Global Wetlands in Response to El Niño Southern Oscillations (ENSO) and Land-Use - Ilyas, Sana; Xu, Xiyan; Jia, Gensuo; Zhang, Anzhi (Frontiers in Earth Science, 2019)
Wetlands are complex and diverse ecosystems, substantially contributing to natural capital. Projected variations in natural and anthropogenic scenarios are likely to alter wetland dynamics by substantially impacting the hydrological and ecosystem functions. This study focuses on monitoring the probable impacts of land use change and El Niño Southern Oscillation (ENSO) variations on wetlands dynamics by analysing the magnitude and extent of global wetland inundation trends during the study period. A microwave dataset was used to study the trends and interannual variability of surface inundation extent of global lakes, rivers, reservoirs and wetland classes. Between 1995 and 2015, the average rate of increase in surface inundation extent of global waterbodies and wetlands of 7029.6 km2 per year occurred with the average inundation of 2.9 million km2. Three periods of significant inter–annual variability 1998–2004, 2005–2009, and 2010–2015 have been observed during 21 years. The maximum contribution of 3.06 million km2 inundation has been recorded during the strong El Niño year of 2010. Swamps flooded forests and coastal wetlands has shown the most significant increase in surface inundation extent. Our results showed a positive lag correlation between Niño 3.4 SST anomalies and surface inundation of different GLWD classes. Moreover, lakes, rivers, reservoirs and wetlands have revealed varying responses to different anthropogenic drivers like cropland, natural vegetation and urban land. Cropland, natural vegetation and barren land buffered region has presented strong negative connection with coastal inundation extent. Whereas swamps demonstrated strongly positive correlation with urban-land and coastal with shrub/grassland land cover type. Through this study the extent of impact projected by climatic oscillations and anthropogenic drivers to water bodies and wetlands can be analysed for well–informed conflict management and decision–making practices for minimizing the human driven impact on natural water systems.